2023
DOI: 10.1021/acscatal.3c04063
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Experimentally Determined Hydrogen Binding Energy with Hydrogen Evolution Activity over Metal Monolayers on Molybdenum Nitride

Kevin K. Turaczy,
Wenjie Liao,
Hansen Mou
et al.

Abstract: It is well established that the hydrogen binding energy (HBE) is a key descriptor for hydrogen evolution reaction (HER) activity, and such a relationship is a useful tool for searching efficient and cost-effective HER catalysts. However, in almost all cases, the HBE values are obtained from density functional theory (DFT) calculations. In this study, temperature-programmed desorption (TPD) was used to experimentally determine the HBE values of metal monolayers supported on molybdenum nitride (Mo2N), and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In addition, such a model system also allows direct verification by experimental studies, as recently demonstrated for nitride-supported Pt for the hydrogen evolution reaction. 24 Using the binding energy of *OH (* denotes adsorbed intermediates) as the OER reactivity descriptor for IrO x /TiN, the OER activity was found to be improved by increasing the Ir coverage from one to three monolayers (MLs), and the trend was confirmed by the experimentally synthesized IrO x /TiN film model catalysts.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, such a model system also allows direct verification by experimental studies, as recently demonstrated for nitride-supported Pt for the hydrogen evolution reaction. 24 Using the binding energy of *OH (* denotes adsorbed intermediates) as the OER reactivity descriptor for IrO x /TiN, the OER activity was found to be improved by increasing the Ir coverage from one to three monolayers (MLs), and the trend was confirmed by the experimentally synthesized IrO x /TiN film model catalysts.…”
Section: Introductionmentioning
confidence: 81%
“…35 Recent work has utilized a combination of fundamental studies of TMN thin films in ultrahigh vacuum (UHV) with electrocatalytic evaluation of the same films or thermocatalytic testing of the corresponding powder catalysts to develop correlations between the configuration and binding strength of surface intermediates and performance under realistic conditions. 36,37…”
Section: Transition Metal Nitride Synthesis and Characterizationmentioning
confidence: 99%
“…It was demonstrated that by depositing 1 ML of Pt or Pd, the required overpotentials to achieve a current density of 10 mA cm −2 shifted to be similar to that of bulk Pt in acidic electrolyte. 37 TPD measurements were used to experimentally determine HBE values for Pt- and Pd-modified Mo 2 N surfaces and correlate them with HER activity. After depositing 1 ML of Pt onto Mo 2 N via physical vapor deposition, desorption temperatures of H 2 at varying heating rates were used to determine the enthalpy of atomic hydrogen adsorption or HBE.…”
Section: Case Studies Of Tmn-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation